Comparative study of sound absorption coefficients of coir/kenaf/sugarcane bagasse fiber reinforced epoxy composites - Jayamani, Elammaran; Soon, Kokheng; Bin Bakri, Muhammad Khusairy; Sinin, Hamdan (Trans Tech Publications Ltd, 2017)
This research focuses on the sound absorption coefficient of three different natural fibers reinforced epoxy composites. The natural fibers used are coconut coir, kenaf, and sugarcane bagasse. All of these fibers were mixed with epoxy resin and hardener with a ratio of 4:1. The mixtures were then poured into a circular mold and compressed by using compression molding technique. It was left for curing for 24 hours at standard room temperature. The results were obtained using the two-microphone transfer functions impedance tube method according to ASTM E1050-12. It is found that as the fiber loading increased, the sound absorption coefficient of the composites increased. 20wt% Coconut coir epoxy composites and 20wt% kenaf fiber epoxy composites have the highest sound absorption coefficient with almost similar sound absorption of 0.078 at 5000Hz. While, 20wt% sugarcane bagasse epoxy composites have sound absorption of 0.075 at 5000Hz.